Sistem Pendukung Keputusan Evaluasi Pemilihan Pemenang Pengadaan Aset dengan Metode Simple Additive Weighting (SAW) - Nugraha, Fajar; Surarso, Bayu; Noranita, Beta (Universitas Diponegoro, 2012)
Procurement of assets by auction requires a decision support in selecting the winning bidder so that decision makers can pick and choose the winner of the auction. This study aims to develop a Decision Support System (DSS), which serves as an aid in decision mak ing in the process of evaluating the winning bidder acquisitions. In order to achieve the purpose of SPK well then helped by using one of the methods in decision-making that is the method of Simple Additive weighting method (SAW) to evaluate alternatives in the provision of asset based decision-making criteria. This method has the advantage criteria (benefits) and cost criteria (cost). Criteria advantage (benefit) is used when considering the aspects of decision making maximum profit. While the cost criteria (cost) is the inver se of the attributes of an advantage, in this draft decision will be looking for a minimal fee. The results may support the decision on the selection of an alternative evaluation of acquisitions winners based on predetermined criteria.Keywords: Acquisitions; Decision support systems; Simple additive weighting